Organizational Justice and Job Satisfaction among Malaysian Workers - Mazidah Mohd Dagang, Azlina Abu Bakar, R Zirwatul Aida R Ibrahim, Jumadil Saputra, Siti Nazilah Mat Ali, (Opción, 2019)
The aim of the study is to investigate the organizational justiceand job satisfaction among Malaysian workers via hierarchicalmultiple regression as a method. The result indicated thatorganizational justice, job control and social support uniquely predictwellbeing (job satisfaction). Interestingly, the pattern of interactionshowed that employees who perceived the interactive effect of high interactional justice and high job control reported lower levels of jobsatisfaction. In conclusion, it is important to promote a just andinclusive organizational working culture which can create a sense ofbelonging, satisfaction and commitment among employees